Drama and the politics of generational conflict in Shakespeare's England - Gearhart, Stephannie S. (Studies in performance and early modern drama., 2020)
Drama and the Politics of Generational Conflict in Shakespeare's England examines the intersection between art and culture and explains how ideas about age circulated in early modern England. Stephannie Gearhart illustrates how a variety of texts - including drama by Shakespeare, Jonson, and Middleton - placed elders' and youths' voices in dialogue with one another to construct the period's ideology of age and shape elder-youth relations.